Cardanol and Eugenol Sourced Sustainable Non-halogen Flame Retardants for Enhanced Stability of Renewable Polybenzoxazines - Appavoo, Divambal; Amarnath, Nagarjuna; Lochab, Bimlesh (Frontiers in Chemistry, 2020)
Olefin bonds participate in co-reaction with the benzoxazine functionality of the monomer and is appeared as one of the strategies to affect the crosslink density of a polybenzoxazine network. In general, the double bond incorporation in starting material is usually catalysed by expensive, rare earth metals affecting the sustainability of the reaction. The natural abundance of feedstocks with inherent double bonds, may be a powerful platform for the development of novel greener structures, thus holds inspiring potential and applicability in polymers. Here, we report the design, synthesis and characterisation of biobased non-halogen flame retardant consisting of naturally occurring phenols, eugenol (E) and cardanol (C). The presence of covalently linked phosphazene (P) core allowed synthesis of hexa-functional flame retardant molecules, abbreviated as EP and CP. The chemical structures of the synthesised EP and CP was confirmed by Fourier transform infrared (FTIR), nuclear magnetic resonance (1H, 13C, 31P NMR) and single crystal XRD (only in the case of EP). Their polymerisation with cardanol sourced tri-oxazine benzoxazine monomer, C-trisapm, was followed by FTIR, NMR and DSC studies. The thermal stability and flame retardant properties of the hybrid phosphazene-benzoxazine copolymers was determined by thermogravimetry analysis (TGA), limiting oxygen index (LOI), vertical burning and smoke density analyses. SEM images of the char residues of the polymers with or without addition of reactive phosphazene molecules confirmed the intumescent flame retarding mechanism. Current work highlights the utility of sustainable origin non-halogen flame retardant (FR) molecules and their utility in polybenzoxazine chemistry.